PENGARUH DISIPLIN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN MELALUI MEDIASI KEPUASAN KERJA PADA KARYAWAN INDOMOBIL NISSAN-DATSUN SOLOBARU - Bryan Filliantoni; Sri Hartono; Sudarwati Sudarwati (JURNAL ILMIAH EDUNOMIKA, 2019)
The study aims to analyze and prove the hypothesis regarding the effect of work discipline and work stress on employee performance through mediating job satisfaction. Case studies were carried out on Indomobil Nissan-Datsun Solobaru employees. Sampling uses census sampling techniques. All respondent populations were sampled with 55 people. Data analysis technique using PLS with WarpPLS 6.0 program. The findings of this study, namely work discipline and work stress have a significant influence on the positive direction of job satisfaction. Job stress and job satisfaction have a significant effect on the positive direction of employee performance. Work discipline does not have a significant effect on employee performance. Job satisfaction is able to be a mediator variable in perfect influence of work discipline on employee performance. Job satisfaction is able to become a variable mediator partially the influence of work stress on employee performance. Keywords: work discipline, work stress, job satisfication and employee performance.